Genomic architecture of resistance to latania scale (H. lataniae) in kiwifruit (A. chinensis var. chinensis) - Flay C; Tahir J; Hilario E; Fraser L; Stannard K; Symonds V; Datson P (BioMed Central Ltd, 2023)
BACKGROUND: Latania scale (Hemiberlesia lataniae Signoret) is an armoured scale insect known to cause damage to kiwifruit plants and fruit, which ultimately reduces crop values and creates post-harvest export and quarantine issues. Resistance to H. lataniae does exist in some commercial cultivars of kiwifruit. However, some of the commercial cultivars bred in New Zealand have not inherited alleles for resistance to H. lataniae carried by their parents. To elucidate the architecture of resistance in the parents and develop molecular markers to assist breeding, these experiments analysed the inheritance of resistance to H. lataniae from families related to commercial cultivars. RESULTS: The first experiment identified a 15.97 Mb genomic region of interest for resistance to H. lataniae in rtGBS data of 3.23 to 19.20 Mb on chromosome 10. A larger population was then QTL mapped, which confirmed the region of interest as the sole locus contributing to H. lataniae resistance. inDel markers mapping the region of low recombination under the QTL peak further narrowed the region associated with H. lataniae resistance to a 5.73 Mb region. CONCLUSIONS: The kiwifruit populations and genomic methods used in this study identify the same non-recombinant region of chromosome 10 which confers resistance of A. chinensis var. chinensis to H. lataniae. The markers developed to target the H. lataniae resistance loci will reduce the amount of costly and time-consuming phenotyping required for breeding H. lataniae scale resistance into new kiwifruit cultivars.
Keywords: Actinidia chinensis; Breeding; Hemiberlesia lataniae; Kiwifruit; Molecular; Resistance; Scale; Humans; Fruit; Plant Breeding; Genomics; Genome, Plant; New Zealand; Actinidia